Ultrasound-guided technique and efficacy of alcohol combined with pingyangmycin sclerotherapy for lymphatic malformations in children - Hong-Xia Zhang; Mei-Ye Li; Xin Li; Jing-Yu Chen; Lin-Ya Lv; Jun Zhang; Zhen-Zhen Zhao; Yi-Fei Du; Liang Peng; Jian-Wu Zhou; Jian Sun; Yao Zhang; et al. (Asian Journal of Surgery, 2025)
Objective: The effects of sclerotherapy on microcystic lymphatic malformations (LMs) and mixed cystic LMs are not as good as those on macrocystic LMs. Therefore, we have designed a study to investigate the effectiveness and safety of a method involving precise injection of ethanol under ultrasound guidance to flush the cystic cavity, followed by retention of pingyangmycin in the cavity. Our goal is to enhance treatment efficacy and reduce complications. Methods: From 2022 to 2023, cases were identified through a prospectively compiled database focusing on LMs, followed by a retrospective review. Patients were included in the study if they had LMs that had been treated with sclerotherapy under ultrasound guidance. The location, size, and type of these LMs were meticulously evaluated using ultrasound and magnetic resonance imaging. Under the guidance of ultrasound, employing a 16G syringe containing absolute ethanol, precise injections were administered into the cystic cavity of a LMs for flushing. Following this, the absolute ethanol was immediately extracted, and pingyangmycin was injected into the cavity and retained to facilitate sustained sclerotherapy. We calculated the tumor volume reduction rate, recorded the total number of sclerotherapy treatments, calculated the cure rate and documented complications. Results: The clinical data of 135 patients were collected, and 91 patients met the inclusion criteria, including 49 males and 42 females. Ninety-one patients (4.23 ± 4.03 years, range 0.09–15.92 years) with 100 lesions were included in the study. The preoperative mean volume of LMs is 26.84 ± 63.65 cm3 (range 0.11–578.17 cm3), and the postoperative mean volume is 7.36 ± 46.93 cm3 (range 0–460.83 cm3, P < 0.01). The effective rate of single injection is 91.00 %, including microcystic LMs (92.40 %), and mixed cystic LMs (88.20 %). The total effective rate is 100 %. An average treatment course of 1.12 sessions (range 1–3) per patient. The dose of pingyangmycin was 2.05 ± 1.40 ml. The incidence of adverse reactions is 4.40 % (4/91), which is only mild and recover after symptomatic treatment. Conclusion: Ultrasound-guided lavage of LMs cysts with absolute ethanol and retention of pingyangmycin within the cysts, and accurate intracavitary injection have obvious effects and low incidence of adverse reactions after a single treatment of children with multiple cystic LMs, which is a safe and effective measure.